Analysis of Financial Performance at the Jimbaraya Multipurpose Cooperative Period 2018-2020 - Firda Mayang Aldira; N N Yintayani; M D Saputra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Financial performance is one of the important factors in the company. Good financial performance can be assessed from the results of the analysis that obtain a percentage in accordance with the standards that have been set. the results of the analysis can assist cooperatives in making appropriate plans and policies in achieving the vision and mission of the cooperative. The research aims to analyze the level of financial performance movement and the health of cooperatives based on the liquidity ratio, solvency ratio, activity ratio and profitability ratio with period from 2018-2020 in accordance with the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia number 06/Per/M/KUKM/V/2006. This research uses a qualitative approach. The results showed that the liquidity ratio is measured using the current ratio and the quick ratio obtains a fairly healthy result because the cooperative is able to guarantee the payment of its current debt. The solvability ratio is measured using the total debt to total assets ratio has fluctuated, where the assets are insufficient to guarantee the cooperative's debt, then measured using the total debt to total equity ratio, there is some less owned capital to guarantee the cooperative's debt. The activity ratio based on the total assets turnover ratio obtained unhealthy results because the sales results obtained were very small. The profitability ratio is measured using return on assets and return on equity has decreased because it is caused by a decrease in profits obtained by cooperatives.